A prospective analysis of the risk factors and the perinatal outcome of preterm labour - Mathew, Sunitha Mary; Kumar, Ajay (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Preterm labour is a challenging complication encountered by obstetricians. The dictum prevention is better than cure well applies for preterm labour also, hence the importance of knowing the risk factors. Infection is one treatable, thus preventable risk factor. Methods: Prospective cohort study involving 75 antenatals at gestational age from 28 to 36+6 weeks. After getting clearance from institutional ethical committee detailed history including history of UTI, excessive vaginal discharge, previous abortions and previous preterm labour and medical complications were collected. Two doses of injection Betamethasone 12 mg 24 hours apart were given for all patients. High vaginal swab was taken from all subjects and results analysed. Neonates are then followed up till discharge. Results: The incidences were higher in primigravidas compared to multiparas. Late preterms (34-36+6 weeks) were the majority in the group. PPROM was the major cause for late preterm births, this was followed by UTI and vaginal infections. Among the high vaginal swab 30.7% were culture positive. E Coli was the most common organism isolated followed by Staphylococcus Aureus, Klebsiella, and MRSA. Hyperbilirubinemia was the most common neonatal complication. Out of 7 neonatal deaths 6 were due to RDS and one was extremely preterm newborn. Women who delivered at least 24 hours after initiation of steroid were considered steroid covered group. Steroid covered group had lesser incidence of RDS with P value of 0.001which was statistically significant. Conclusions: UTI and vaginal infections were major risk factors for preterm labour and should be tackled antenatally. High vaginal swab should be taken for threatened preterm labour especially early preterm. Betamethasone administration causes a definite reduction in the incidence of RDS. Induce PPROM after 36 weeks to reduce late preterm complications provided there is no chorioamnionitis.